THU0527 Pediatrician and adult rheumatologist collaborating in a multidisciplinary reuma-ped clinic. is this transitional care model effective?. (15th June 2017) - Collado, P; Rubio, A; Diaz-Delgado, R; Calvo, C; Mustienes, R; Rey, F; Bonilla, C; Cruz, E
Abstract : Background: Transitional care should be a planned movement of adolescents with chronic diseases from child-centred to adult-oriented health care system. Recently a EULAR/PReS taskforce has developed the first international set of recommendations and standards for transitional care 1 . Objectives: To describe the results from a specific transitional care programme. Methods: The current transitional care programme includes a multidisciplinary PED-REUMA clinic (MPRC) weekly and a non-defined period of rheumatologic follow-ups by the same rheumatologist of MPRC. The transitional care team is composed of two pediatricians, one adult rheumatologist -as transition coordinator-, a clinical nurse specialist and administrative support, as well as a psychologist and physiotherapists. Clinical information and therapies were collected throughout the disease course, and the HEADSS method of psychosocial interviewing has been included recently. Population of the present study included young patients (YP) from that programme who are going to transfer to adult-oriented health care system. Descriptive study of socio-demographics and clinic features was included, as well as patients' adherence. YP confidence to be transferred and satisfaction with the current transitional process were measured using on a scale of 0 to 10. In patients suffering from juvenile idiopathic arthritis (JIA), clinical status of disease activity and clinical remission and CHAQ were tested before transfer. Results: Twenty-seven YP with female predominance (63%) were included. The average age was 21±3 yo at time of a planned transfer and 16±3.4 yo at inclusion to the MPRC. JIA was the commonest condition whereas dermatomyositis was uncommon. Up to 63% patients required some DMARDs during the MPRC follow-up, but only a 37% needs maintained immunosuppressive therapies and three (11%) patients required changing the therapeutic target before transfer. YP adherence to rheumatologist appointments was high. Regarding HEADSS data: most YP were students and living at family home, around 50% gave up sports or other activities due to homework or exams, 29% of YP occasionally drank some alcohol but none used tobacco, and 47% of YP felt sad or down once in a while. Patient's confidence to be transferred was 7.7±2.1 (mean±SD; min-max: 2–10). YP showed high satisfaction with the current transitional process, 9.7±0.4 (min-max: 9–10). Before transfer, 17 patients with JIA showed a mean±SD value of JADAS10 of 2±5 (min-max, 0–18), clinical remission on/off medication was 23% and 53% respectively. Mostly functional status reported by patient was low, YP-rated CHAQ (mean 0.06; min-max, 0.0–0.75). Conclusions: To the best of our knowledge, this is the first study evaluating a Spanish transitional care programme. The study reports a positive impact across adolescence of our transitional care model in a real life situation. Implementation of recommendations depended on the local available resources. References: Foster HE. EULAR/PReS standards and recommendations for the transitional care of young people with juvenile-onset rheumatic diseases. Ann Rheum Dis Published Online First: [1, November 2016] doi:10.1136/ annrheumdis-2016–210112. Acknowledgements: Beatriz Jimenez. Auxiliary to the clinical nurse specialist and administrative support of Rheumatology Department. Disclosure of Interest: None declared